The Certainty And Legal Protection To The Buyer's Auction Of The Mortgage Right Object On Online Auctions At The Service Of Wealth State Office And Auction (KPKNL) - Arif Budi Pamungkas; Zaldy Kurniawan; Djauhari Djauhari (Jurnal Akta, 2018)
An auction is an activity of selling of goods in public by means of a verbal-bid to get the higher price or to get lower prices and the price quote can be done in a closed and written. This is done by the way of collecting the prospective buyers of the auction led by officials of the auction. In this case, the intended auction was the sale of goods that are held publicly. The auction, according to the regulations of security right, is when the debtor made a breach, the holder of the security rights have the right to sell the security rights’ objects over its own power through a public auction as well as taking payment of account receivable from the sale proceeds. An auction is an alternative to the sale of an undertaken asset by way of inviting prospective buyers at a particular time and place in which the last highest bidder in writing or orally is determined as the winner. The author used socio-legal research as his research method. To meet the forth standards set by the law, the auction should be widely announced to the public, either through printed file, electronic or visual. A legal certainty as a basis which concerned with propriety and justice is very closely related to the principle of auction sales in another. As the formulation of the problem of the form of identification of the problem, namely how the legal protection of the auction buyers encountered the obstacles as well as the solution.Keywords: Auction; Legal Protection; Mortgage Right